Superresolution imaging reveals structurally distinct periodic patterns of chromatin along pachytene chromosomes - Prakash, Kirti; Fournier, David; Redl, Stefan; Best, Gerrit; Borsos, Máté; Tiwari, Vijay K.; Tachibana-Konwalski, Kikuë; Ketting, René F.; Parekh, Sapun H.; Cremer, Christoph; Birk, Udo J. (Proceedings of the National Academy of Sciences of the United States of America, 2015)
During meiosis, homologous chromosomes associate to form the synaptonemal complex (SC), a structure essential for fertility. Information about the epigenetic features of chromatin within this structure at the level of superresolution microscopy is largely lacking. We combined single-molecule localization microscopy (SMLM) with quantitative analytical methods to describe the epigenetic landscape of meiotic chromosomes at the pachytene stage in mouse oocytes. DNA is found to be nonrandomly distributed along the length of the SC in condensed clusters. Periodic clusters of repressive chromatin [trimethylation of histone H3 at lysine (Lys) 27 (H3K27me3)] are found at 500-nm intervals along the SC, whereas one of the ends of the SC displays a large and dense cluster of centromeric histone mark [trimethylation of histone H3 at Lys 9 (H3K9me3)]. Chromatin associated with active transcription [trimethylation of histone H3 at Lys 4 (H3K4me3)] is arranged in a radial hair-like loop pattern emerging laterally from the SC. These loops seem to be punctuated with small clusters of H3K4me3 with an average spread larger than their periodicity. Our findings indicate that the nanoscale structure of the pachytene chromosomes is constrained by periodic patterns of chromatin marks, whose function in recombination and higher order genome organization is yet to be elucidated.
Gesehen am 09.07.2020